Dielectric and electro-optical properties of ferric oxide nanoparticles doped 4-octyloxy-4' cyanobiphenyl liquid crystal-based nanocomposites for advanced display systems. Issue 7 (28th May 2021) - Tripathi, Pankaj Kumar; Roy, Aradhana; Misra, Abhishek Kumar; Pandey, Kamal Kumar; Manohar, Rajiv; Negi, Y. S.
ABSTRACT: Doping of ferric oxide (Fe2 O3 ) nanoparticles in 4-octyloxy-4ʹ cyanobiphenyl (8OCB) liquid crystal compound embedded in sample cells formed by photolithographic technique. The dielectric spectroscopy is investigated over a wide frequency from 500 Hz to 10 MHz. Various parameters such as switching time (τon and τoff ), dielectric permittivity (ε'), dielectric loss (ε"), relaxation frequency and optical texture of pristine 8OCB and 8OCB-Fe2 O3 nanocomposite were investigated as functions of frequency and temperature. Moreover, splay elastic constant (k11 ), rotational viscosity (γ) as a function of weight % of Fe2 O3 NPs have also been investigated. These values are strongly affected by the presence of Fe2 O3 NPs due to the enhancement of molecular ordering. The doped Fe2 O3 NPs within the 8OCB LC may align along the director ñ strongly favours a splay distortion of ñ as the orientational order is increased. Optical image showed an improved molecular ordering of 8OCB with doping of Fe2 O3 NPs. The dielectric anisotropy (Δε) of 8OCB-Fe2 O3 nanocomposites was found to be reduced whereas threshold voltage (Vth ) increased with increasing the doping of Fe2 O3 NPs within the 8OCB. In addition to this, Fe2 O3 NPs alter the magnitude of the perpendicular and parallel component of dielectric permittivity of nanocomposite. Abstract :